ANALISIS EFEKTIVITAS PAJAK SEBELUM DAN SELAMA PENERAPAN PENARIKAN PAJAK KELILING TERHADAP PENDAPATAN ASLI DAERAH KOTA KEDIRI (Studi Pada Realisasi Pajak Kota Kediri Tahun 2014 - 2017) - Aprian Ibrahim; Agus Salim; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purposes of this research are: 1) To analyze the effectiveness of Tax Withdrawal Tax on Local Tax Target. 2) To analyze how big the rate of growth before and during the application of withdrawal of Mobile Tax on Local Revenue. 3) Projecting the capacity of local governments in determining tax targets to improve local indigenous participation. This research uses quantitative research method by using Secondary Data. The sample of this research is collecting local revenue data around 6 years.The results of this study show that: 1) There is a level of effectiveness in before and during the application of mobile taxes can be deduced on the increasing yield every year. 2) there is a level of effectiveness on before and during the implementation of mobile taxing can be concluded on the results every year has an increase of 14% and 3) There has been an increase contribution in the realization of taxes over the three-year period of Kediri municipal government has increased by proven based on projection analysis. This result indicates that a level of effectiveness in before and during the application of mobile taxes can be deduced on the increasing yield every year. Keywords: Comparing before and after, income growth rate, and Contribution.